2018
DOI: 10.1186/s12873-018-0201-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute coronary syndrome in emergency departments: a cross sectional multicenter study (Tunisia)

Abstract: BackgroundWe aimed to describe diagnosed acute coronary syndrome (ACS) and its care management and outcomes in emergency departments (EDs) and to determine related cardiovascular risk factors (CVRFs).MethodsWe conducted a cross sectional multicenter study that included 1173 adults admitted to EDs for acute chest pain (ACP) in 2015 at 14 sites in Tunisia. Data included patients’ baseline characteristics, diagnosis, treatment and output.ResultsACS represented 49.7% of non-traumatic chest pain [95% CI: 46.7–52.6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In another study, Mohan [30] reported that although 96% of patients were aware of ambulance services, only 5.3% of patients used an ambulance for transport. In several other studies, presenting directly to a tertiary facility significantly reduced mean treatment time versus those who were initially seen at a general hospital or by a primary clinician [19] , [20] , [21] , [26] , [27] , [28] , [34] , [35] , [37] , [41] . There was general agreement among studies that a lack of available reperfusion centers outside of major urban areas, limited diagnostic resources (EKG, cardiac enzymes) and adequately trained clinicians to recognize ACS prolonged symptom onset to treatment time [21] , [26] , [27] , [28] , [30] , [31] , [42] , [43] .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In another study, Mohan [30] reported that although 96% of patients were aware of ambulance services, only 5.3% of patients used an ambulance for transport. In several other studies, presenting directly to a tertiary facility significantly reduced mean treatment time versus those who were initially seen at a general hospital or by a primary clinician [19] , [20] , [21] , [26] , [27] , [28] , [34] , [35] , [37] , [41] . There was general agreement among studies that a lack of available reperfusion centers outside of major urban areas, limited diagnostic resources (EKG, cardiac enzymes) and adequately trained clinicians to recognize ACS prolonged symptom onset to treatment time [21] , [26] , [27] , [28] , [30] , [31] , [42] , [43] .…”
Section: Resultsmentioning
confidence: 93%
“…In the majority of studies, male gender and younger age were associated with earlier treatment of ACS compared to females and older adults, respectively [19] , [23] , [31] , [33] , [34] , [35] . Several studies reported however, that there were no differences in treatment for ACS due to either gender or age characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies had confirmed that this variable has a significant effect on the long-term prognosis of patients with AMI. 30 32 The higher the Killip grading, the worse the prognosis of patients with AMI. In this study, with the increase in PASP levels, the proportion of patients with Killip I grades gradually decreased, and the proportion of patients with grade II to IV gradually increased.…”
Section: Discussionmentioning
confidence: 99%